The Predicted ABC Transporter AbcEDCBA Is Required for Type IV Secretion System Expression and Lysosomal Evasion by Brucella ovis - Silva, Teane M. A. (Public Library of Science, 2014)

(untitled) (PLoS One)
Brucella ovis is a major cause of reproductive failure in rams and it is one of the few well-described Brucella species that is not zoonotic. Previous work showed that a B. ovis mutant lacking a species-specific ABC transporter (ΔabcBA) was attenuated in mice and was unable to survive in macrophages. The aim of this study was to evaluate the role of this ABC transporter during intracellular survival of B. ovis. In HeLa cells, B. ovis WT was able to survive and replicate at later time point (48 hpi), whereas an ΔabcBA mutant was attenuated at 24 hpi. The reduced survival of the ΔabcBA mutant was associated with a decreased ability to exclude the lysosomal marker LAMP1 from its vacuolar membrane, suggesting a failure to establish a replicative niche. The ΔabcBA mutant showed a reduced abundance of the Type IV secretion system (T4SS) proteins VirB8 and VirB11 in both rich and acid media, when compared to WT B. ovis. However, mRNA levels of virB1, virB8, hutC, and vjbR were similar in both strains. These results support the notion that the ABC transporter encoded by abcEDCBA or its transported substrate acts at a post-transcriptional level to promote the optimal expression of the B. ovis T4SS within infected host cells.